Early Warning and Rapid Response System for Pests and Diseases in Ghana - Honger, Joseph; Gariba, Awudu Amadu; Osae, Michael; Tepa-Yotto, Ghislain (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The Ghana Cluster of the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) project, led by the International Institute for Tropical Agriculture (IITA) and its partners are working on an Early Warning and Rapid Response System for Pests and Diseases (EWRRS-PD) to enhance communication, data sharing, and preparedness against new risks. Following several preparatory meetings, a workshop was held to validate a partnership agreement between eleven public and private sector institutions whose core mandate relates to the subject. This validation workshop was followed by a signing ceremony where heads of the partner institutions demonstrated their commitment to this cause by signing the Memorandum of Understanding (MOU). This commitment is a testament to the importance placed on an EWRRS-PD in Ghana. The AICCRA Ghana Cluster is also leading capacity building for relevant stakeholders in reporting, risk knowledge generation, risk communication, monitoring and warning, risk assessment, and risk response dissemination. This situational analysis highlights the ongoing efforts to improve plant pests and diseases surveillance in Ghana and underscores the potential for collaboration in developing an effective EWRRS-PD in Ghana.